Mastering Perl - Foy, Brian D. (Sebastopol, CA : O'Reilly Media, 2014)
"Take the next step toward Perl mastery with advanced concepts that make coding easier, maintenance simpler, and execution faster. Mastering Perl isn't a collection of clever tricks, but a way of thinking about Perl programming for solving debugging, configuration, and many other real-world problems you'll encounter as a working programmer. The third in O'Reilly's series of landmark Perl tutorials (after Learning Perl and Intermediate Perl), this fully upated edition pulls everything together and helps you bend Perl to your will."--Publisher's description.
Advanced regular expressions -- Secure programming techniques -- Perl debuggers -- Profiling Perl -- Benchmarking Perl -- Cleaning up Perl -- Symbol tables and typeglobs -- Dynamic subroutines -- Modifying and jury-rigging modules -- Configuring Perl programs -- Detecting and reporting errors -- Logging -- Data persistence -- Working with Pod -- Working with bits -- The magic of tied variables -- Modules as programs.
Online resource; title from PDF title page (Safari, viewed Jan. 17, 2014).
Includes bibliographical references and indexes.
Keywords: Perl (Computer program language); Perl (Langage de programmation); COMPUTERS -- Programming Languages -- C♯; COMPUTERS -- Programming Languages -- Java; COMPUTERS -- Programming Languages -- Pascal; Perl (Computer program language)